Impact of high and low concentration of fly ash amended soil on physico‐chemical properties of biodiesel produced from Jatropha curcas. Issue 4 (7th March 2022) - Mohan, Sumedha; Raj, Seema
Abstract: In the prevailing era of stagnating crude oils, depleting fossil fuel reserves and ever rising demand, vegetable oils that are non‐edible serve as a viable alternative to fossil fuels. Being renewable, they can be easily produced, are available in abundance, give carbon dioxide free emissions and hold tremendous potential to be transesterified to produce biodiesel. The non‐edible Jatropha curcas oil is a significant source for biodiesel production as it is easily grown and is cost‐effective. However, mass‐scale production is still a milestone to be reached for its practical usage. Herein, it was aimed to optimize the best composition of the base material by varying fly ash and soil concentrations for increased biodiesel efficiency from Jatropha in an extensive 5‐year study. The significance of fly ash in soil was understood by performing a series of physico‐chemical analysis of biodiesel prepared from Jatropha seed oil grown in different compositions of fly ash amended soil. It was observed that base material II plant gave 350 g seeds and 157 ml of seed oil in third year, whereas, the base material III plants gave 250 g seeds and 94 ml seed oil. Additionally, correlation analysis showed that seed yield, Jatropha oil extracted, and biodiesel production was positively correlated with percent metal uptake by plants from base materials. The addition of 25% fly ash with soil enhanced the yield of seeds and the quality of biodiesel produced in accordance with the American Standards of Testing and Materials (ASTM) which proves sustainable energy production.